The Effectiveness of Quizwhizzer Learning Media on Students' Mastery of GoiState Senior High School 4 Padang - Adisty Mutia Khonita; Hendri Zalman (Universitas Negeri Padang, 2026)
The author's observation that students struggled to recall terminology led to the conduct of this study. The learning media used were less varied in Japanese language learning. Finding out how much of an effect Quizwhizzer had on high school students' Japanese vocabulary knowledge was the driving force for this research. In this work, the researchers used a quantitative technique and a pre-experimental design. The experimental design was a One-Group Pretest-Posttest Design. A total of 36 students made up the research sample for this XII F.5 study. This research used a fair and methodical sampling technique. This study was built using both pre-test and post-test data. A twenty-question multiple-choice exam was used as the research instrument. A mean score of 70.27 on the pretest and 81.38 on the posttest were obtained. The results on the pretest had a standard deviation of 9.92 and those on the posttest of 9.82. A significant level of 0.000 <0.05 was shown by the paired sample t-test findings. Furthermore, after using Quizwhizzer, students' Japanese vocabulary mastery improved. These data demonstrate that Quizwhizzer is effective in improving students' vocabulary mastery.